EVALUASI PELAKSANAAN PROGRAM PELAYANAN LANJUT USIA DI UNIT PELAKSANA TEKNIS PELAYANAN SOSIAL TUNA RUNGU WICARA DAN LANJUT USIA PEMATANGSIANTAR - RINI LESTARI SIAHAAN (Welfare StatE, 2013)
The increasing life expectancy of the people of Indonesia had an impact consequence of the increasing elderly population from year to year, giving rise to the need social services for the elderly in old age filled with peace, especially for the elderly and vulnerable displaced displaced. To overcome the problems of older persons in this thing department social persue a container or vehicle to accommodate the elderly in a institution. In the containerthat built, the elderly provided services and guidance that can help elderly in meeting their needs. The research was conducted at the Technical Implementation Unit (UPT) Social Services Speech and Deaf Seniors Pematangsiantar. A total of 32 seniors who become residents of UPT is the elderly who no longer have kerluarga and abandoned, and the elderly are experiencing economic problems and need assistance in meeting their needs. This study uses descriptive research with a quantitative approaches. To obtain the necessary data, this study used data collection techniques and field studies literature consisting of distributing questionnaires (questionnaire), interview and observation. The results of the data analysis, the authors concluded that the program in the Elderly Care Unit of Social Services Speech and Deaf Seniors Pematangsiantar its implementation has been performing well. This is evident from the answers of the respondents to the implementation of the program itself elderly services ranging from health care, spiritual care, and social services is already showing good results and the program can be said to be very beneficial for the elderly. Keywords: evaluation, social services, elderly